PTU-123 Endorings assisted colonoscopy versus standard colonoscopy for polyp detection: a randomised controlled trial. Issue 2 (June 2019) - Thayalasekaran, Sreedhari; Bhattacharyya, Rupam; Chedgy, Fergus; Basford, Peter; Alkandari, Asma; Subramaniam, Sharmila; Kandiah, Kesavan; Thursby-Pelham, Fergus; Ellis, Richard; Coda, Sergio; Goggin, Patrick; Longcroft-Wheaton, Gaius; et al.
Abstract : Introduction: The Endorings TM is a distal attachment consisting of two layers of circular flexible rings that evert mucosal folds. Aims; to investigate if Endorings Colonoscopy (ER) improves polyp and adenoma detection compared to standard colonoscopy (SC). Methods: This multi-centre, parallel group, randomized controlled trial included screening, surveillance and symptomatic patients. Primary outcome; number of polyps per patient. Secondary outcomes; number of adenomas per patient, adenoma/polyp detection rates and withdrawal times. Results: Total of 556 patients (214 females, 342 males) randomized to ER (275) or SC (281). Mean age 67. Colonoscopy completed 532/556 (96%) cases. EndoRings removed in 74/275 (27%) patients. In 66/74 (89%) cases removal was performed due to difficulties with sigmoid intubation. Remainder removed to facilitate retroflexion or polyp removal/retrieval. Total number of polyps in ER limb 571 vs 444 in SC limb. Total number of adenomas in ER limb 361 vs 343 for SC limb. Our study showed a statistically significant difference in the mean number of polyps per patient in both the Intention to Treat (ITT) (1.8 SC vs 2.1 ER, p-value 0.02) and Per Protocol (PP) (1.8 SC vs 2.25 ER, p-value 0.009). There was a trend towards a greater polyp detection rate in the ER colonoscopy (67.5% SC vs 75.2% ER, p-value 0.05). Conclusions: Despite the high removal rate of Endorings, there was a statistically significant increase in the mean number of polyps in the ER limb compared to the SC limb. Our study shows promise for the EndoRings TM device to improve polyp detection.